DEVELOPMENT OF A MANUAL PROCEDURE FOR USING VIDEO-BASED E-RESOURCES (DIGITAL LIBRARY) ON THE JAMBI UNIVERSITY LIBRARY WEBSITE - Mahdianto Mahdianto; Zurweni Zurweni; Sofyan Sofyan (SEAN Institute, 2023)
Through its website, Universitas Jambi Library (UNJA Library) should be able to provide information on how to access its E-resources. By fulfilling the guidance information, it is hoped that it will be able to provide industry-based services 4.0, one way is to make a video manual on procedures for using the UNJA library website's E-resources. This was made with the aim that information access activities for all users can be distributed properly and run effectively and efficiently. Many users do not understand how to use the Jambi University library's e-resources. Because this will definitely affect library e-resources, the researcher developed a video-based web-based E-Resources Usage Procedure Manual for using digital libraries at the Jambi University library. The subjects in this study were Jambi University users. This development research procedure refers to the Trollip & Alessi model. To assess the product being developed, a validation test was applied by media experts, material experts, user response questionnaires and to see an increase in knowledge in the use of Jambi University library e-resources.